Delegates from the International Community-Based Adaptation Conference (CBA9) visit to Makueni & Machakos - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
More than 400 delegates from over 90 countries attended the 9th International Community-Based Adaptation Conference (CBA9), and around 160 embarked on a series of field trips over three days before the start of the conference in Nairobi, Kenya. The field trips enabled the participants to explore at first hand issues related to community-based adaptation to climate change, particularly with regards to measuring and enhancing effective adaptation. These photos were taken from two projects: 1.ASARECA project in collaboration with KALRO Katumani supported by World Bank at Kiima Kimwe and Kiboko villages in Makueni and Machakos 2.CCAFS Project in Wote, Makueni Photos: P.Kimeli (CCAFS) and C.Krabbe (CARE).